Design, fabrication and characterization of CMOS ISFET for pH measurements - Chin, Seng Fatt (School of Microelectronic, Universiti Malaysia Perlis, 2009)
This thesis describes the design, simulation, fabrication and characterization of ISFET for pH measurement of an aqueous solution.